The Influence Of Celebrity Endorsers And Electronic Word Of Mouth On Purchase Decision Trust On Lazada Marketplace Surabaya - Fidela Mandasari; Eko Purwanto; Sugeng Purwanto (LPPM Universitas Trunojoyo Madura, 2023)
Celebrity endorsers and electronic word of mouth are essential factors in creating trust and consumer purchase decisions for Lazada. Therefore, this study aims to determine whether celebrity endorsers and electronic word-of-mouth marketing can influence a consumer's purchase decision directly or through trust. The type of data used in this study is quantitative data. The sampling technique used in this study was nonprobability sampling with the purposive sampling method. Thus the sample used was 102 Lazada marketplace customers in Surabaya. The data analysis technique used to process data is SmartPLS. The results of this study show that Celebrity endorsers and Electronic word of mouth have a positive and significant effect on purchase decisions. Furthermore, Celebrity Endorsers and Electronic word of mouth positively and significantly affect purchase decisions through trust